Ectopic expression of miR-182 in chimeric antigen receptor-modified T cells - Carneiro, Mayra (2016)
Instituto Nacional de Câncer José Alencar Gomes da Silva. Programa de Carcinogênese Molecular. Rio de Janeiro, RJ, Brasil.